1998
DOI: 10.4131/jshpreview.7.1147
|View full text |Cite
|
Sign up to set email alerts
|

Filling-Isotherms in Clathrate-Hydrates.

Abstract: Clathrate hydrates of N2 and CO2 were investigated in situ as a function of gas pressure by neutron powder diffraction. Gas pressure cells developed specifically for this work were employed.The pressure dependency of the filling of the different cages in these clathrate hydrates was established. In contrast to some earlier indirect evidence the small cages in CO2 clathrate hydrate are partly filled, however the generally accepted Langmuir-behaviour of the filling is violated in this case. Likewise, instead of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
30
3

Year Published

2002
2002
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(36 citation statements)
references
References 5 publications
3
30
3
Order By: Relevance
“…Thermodynamic modeling favors the latter. However, in neutron diffraction study of clathrate cited above Kuhs et al(1997) reported an increase in X-site occupancy by CO 2 in type-I clathrate at 273 K between 15 and 25 bars that agreed with theoretical predictions; whereas in a subsequent study Kuhs et al (1998) reported an improbable decrease in X-site occupancy between 25 and 40 bars with the lower occupancy remaining constant to 60 bars. These data may indicate an order/disorder transformation related to filling of the guest sites between 25 and 40 bars at 273 K. Such a transformation would favor I␣3 I␤.…”
Section: A Solid-state Phase Transformation?mentioning
confidence: 76%
“…Thermodynamic modeling favors the latter. However, in neutron diffraction study of clathrate cited above Kuhs et al(1997) reported an increase in X-site occupancy by CO 2 in type-I clathrate at 273 K between 15 and 25 bars that agreed with theoretical predictions; whereas in a subsequent study Kuhs et al (1998) reported an improbable decrease in X-site occupancy between 25 and 40 bars with the lower occupancy remaining constant to 60 bars. These data may indicate an order/disorder transformation related to filling of the guest sites between 25 and 40 bars at 273 K. Such a transformation would favor I␣3 I␤.…”
Section: A Solid-state Phase Transformation?mentioning
confidence: 76%
“…It may be noted that recent experiments on CO 2 clathrate have indicated that a compensation of mechanical compression and filling-induced expansion may lead to a net increase of lattice constants with increased gas pressure. 29 Despite a slightly larger cage filling in the O 2 case and the almost identical molecular size for N 2 and O 2 in the free gas phase, 58,59 the O 2 -clathrate lattice constant is found to be significantly smaller than that of N 2 -clathrate ͑Table III, Fig. 3͒.…”
Section: A Lattice Constants and Compressibilitymentioning
confidence: 93%
“…44 -46 All these experiments were performed on recovered samples and did not provide structural details like cage sizes and cage fillings, which are of considerable importance for a complete understanding of natural air hydrates. 35,36 In a preliminary study using a more limited data set 28,29 we reported on deviations from the generally assumed Langmuir filling behavior of N 2clathrates and observed the co-formation of metastable type I N 2 -clathrates formed at 273 K at pressures above 560 bar together with the usual type II clathrate. In contrast to theoretical predictions of the stability field of type I N 2clathrate 47 it was found that the initially obtained type I structure transformed completely into type II over periods of several weeks up to several months and must, therefore, be considered as metastable.…”
Section: Introductionmentioning
confidence: 96%
See 2 more Smart Citations